Genetic modeling of ELP1-associated Sonic hedgehog medulloblastoma identifies MDM2 as a selective therapeutic target - Ahmad, Shiekh Tanveer; Li, Yiran; Garcia-Lopez, Jesus; Gudenas, Brian L.; Hadley, Jennifer; Paul, Leena; Wu, Stephanie C.; Refaat, Alaa; Kojic, Marija; Batts, Melissa; Soliman, Taha; Pitre, Aaron; et al. (Cancer cell, 2025)
Germline loss-of-function (LOF) variants in Elongator acetyltransferase complex subunit 1 (ELP1) are the most prevalent predisposing genetic events in childhood medulloblastoma (MB), accounting for ∼30% of the Sonic hedgehog (SHH) 3 subtype. The mechanism(s) by which germline ELP1 deficiency provokes SHH-MB pathogenesis remain unknown. Genetically engineered mice mimicking heterozygous Elp1 LOF (Elp1HET) seen in affected germline carriers exhibit hallmark features of premalignancy in cerebellar granule neuron progenitors (GNPs), including increased DNA replication stress, genomic instability, accelerated cell cycle, and stalled differentiation. Orthotopic transplantation of Elp1HET GNPs harboring somatic Ptch1 inactivation yields SHH-MB-like tumors with compromised p53 signaling, providing a plausible explanation for the exclusivity of ELP1-associated MBs in the SHH-3 subtype. Preclinical treatment of ELP1-mutant patient-derived xenografts with an FDA-approved MDM2 inhibitor reactivates p53-dependent apoptosis and extends survival. Our findings functionally substantiate the role of ELP1 deficiency in SHH-MB predisposition and nominate therapeutics targeting MDM2 as a rational treatment option.